Michael Klim's Full Stroke at 130 m of His 200 m Freestyle Gold Medal Race at the 1998 Perth World Championships - Rushall, B. S.
Video pictures (18 frames) and the appropriate technical/ biomechanical explanations for Michael Klim's full stroke at 130 m of his 200 m freestyle Gold Medal Race at the 1998 Perth World Championships. Michael Klim is a very powerful young man. His remarkable upper body strength perhaps make it possible for him to swim with a straight arm recovery and to accommodate the large lateral forces it generates. But one is set to wondering about the energy costs, loss of propulsive efficiency and acceleration, particularly in the initial stages of the arm strokes, and other compromises that occur. It would not be advisable for many swimmers to attempt copying this swimming style. Perhaps one of the admirable features of Michael Klim's stroke is his consistently good streamlining. Within reason, his torso, hips, and thighs remain horizontal and in line. His hips up -- head down position facilitates minimal frontal resistance. However, it is unlikely that Michael Klim's performances will improve unless there are appropriate technique changes.